2021
DOI: 10.3389/fphys.2021.718568
|View full text |Cite
|
Sign up to set email alerts
|

Altered Vascular Adaptations to Pregnancy in a Rat Model of Advanced Maternal Age

Abstract: Advanced maternal age (≥35 years old) increases the risk of pregnancy complications such as preeclampsia and fetal growth restriction. We previously demonstrated vascular dysfunction and abnormal pregnancy outcomes in a rat model of advanced maternal age. However, vascular adaptations to pregnancy in aging were not studied. We hypothesize that advanced maternal age is associated with a more vasoconstrictive phenotype due to reduced nitric oxide (NO) and increased activity of matrix metalloproteinases (MMPs), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
(124 reference statements)
0
5
1
1
Order By: Relevance
“…These findings contrast with other studies, which showed that TUDCA increased NO bioavailability by reducing ER stress and improved vascular function in mesenteric arteries and aorta from tunicamycin-treated mice and in db/db mice [44,56]. A potential explanation for these differences in vascular outcomes after TUDCA treatment could be that the other studies were conducted in non-pregnant rodents, and chemically induced ER stress causes pronounced vascular endothelial dysfunction with reduced NO, which is not what we observed with advanced maternal age rats [14]. Further, the rat age of our model may not be sufficiently old enough to affect endothelium-dependent relaxation in mesenteric arteries, as it is possible that age-related vascular changes are ongoing.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…These findings contrast with other studies, which showed that TUDCA increased NO bioavailability by reducing ER stress and improved vascular function in mesenteric arteries and aorta from tunicamycin-treated mice and in db/db mice [44,56]. A potential explanation for these differences in vascular outcomes after TUDCA treatment could be that the other studies were conducted in non-pregnant rodents, and chemically induced ER stress causes pronounced vascular endothelial dysfunction with reduced NO, which is not what we observed with advanced maternal age rats [14]. Further, the rat age of our model may not be sufficiently old enough to affect endothelium-dependent relaxation in mesenteric arteries, as it is possible that age-related vascular changes are ongoing.…”
Section: Discussioncontrasting
confidence: 89%
“…In a previous study, we observed altered vascular to pregnancy in mesenteric arteries of aged dams compared to young dams [ 14 ]. Given the association of ER stress with adverse pregnancy outcomes ([ 27 , 47 ], we speculated that ER stress may be involved in mediating this vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a previously established rat model of advanced maternal age [ 38 , 63 , 64 , 65 ]. Aged rats at 9.5 months of age correspond to ~35 years of age in humans, based on milestones such as weaning, skeletal and sexual maturity, and reproductive senescence, and young control rats at 3.5–4 months of age correspond to ~early reproductive maturity in humans [ 63 , 66 ].…”
Section: Methodsmentioning
confidence: 99%